2022
DOI: 10.1021/acs.cgd.2c00187
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Tunability of Zero-Dimensional Organic–Inorganic Metal Halides Utilizing the m-Xylylenediammonium Cation: MXD2PbI6, MXDBiI5, and MXD3Bi2Br12·2H2O

Abstract: Over the past decade, the efficiency of photovoltaic devices based on CH 3 NH 3 PbI 3 have dramatically increased. This has driven research efforts in all areas, from the discovery of materials to film processing to long-term device stability studies. Here, we report the synthesis and structure of three new “zero dimensional” organic–inorganic metal halides which use the meta-xylylenediammonium (MXD) cation: MXD 2 PbI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
5
1
Order By: Relevance
“…We found that (MXD)BiI 5 constructed with MXD 2+ cation has a zerodimensional (0 D) structure and crystallized in a centrosymmetry space group (P-1) (Figure S1, Supporting Information). [27] This is different from previous reported HPs (x-AMPY)BiI 5 and (x-AMP)BiI 5 (AMPY is (aminomethyl)pyridinium, AMP is (aminomethyl)piperidinium), which are also constructed with aromatic and aliphatic diammoniums, but both have 1 D chainlike structure. [25] In our system, the spatial confinement effect of the inorganic skeleton on organic ammonium cations in (MXD)BiI 5 is not as strong as in (1,3-BMACH)BiI 5 .…”
Section: Crystal Structure Characterizationcontrasting
confidence: 65%
“…We found that (MXD)BiI 5 constructed with MXD 2+ cation has a zerodimensional (0 D) structure and crystallized in a centrosymmetry space group (P-1) (Figure S1, Supporting Information). [27] This is different from previous reported HPs (x-AMPY)BiI 5 and (x-AMP)BiI 5 (AMPY is (aminomethyl)pyridinium, AMP is (aminomethyl)piperidinium), which are also constructed with aromatic and aliphatic diammoniums, but both have 1 D chainlike structure. [25] In our system, the spatial confinement effect of the inorganic skeleton on organic ammonium cations in (MXD)BiI 5 is not as strong as in (1,3-BMACH)BiI 5 .…”
Section: Crystal Structure Characterizationcontrasting
confidence: 65%
“…The lead-based HPs constructed with diammonium cation 1,3-xylylenediammonium did not form a 2D DJ structure but existed as a zerodimensional (0D) structure, and all crystallized in a centrosymmetric space group. 47 From the above analysis, it can be seen that the configuration of diammonium cations not only affects the dimension of the obtained HPs but also affects its structural symmetry.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…[ 15 ] This value close to those for some reported 0D binuclear BHPs, like ( R ‐1‐(4‐fluoro)‐phenylethylammonium) 4 Bi 2 I 10 (2.09 eV) [ 16 ] and (meta‐xylylenediammonium)BiI 5 (2.15 eV). [ 17 ] Considering the chiral‐polar structure of 1 R / 1 S , their chiroptical features were studied. As shown in Figure 2b, the obvious circular dichroism (CD) signals for 1 R and 1 S films (Figure S10, Supporting Information) were observed at the same wavelengths but with opposite values.…”
Section: Resultsmentioning
confidence: 99%